A Stylistic Analysis of The Poem “The Passionate Shepherd to His Love” by Christopher Marlow - Tjuana, Ardhitya Nugrahatama; Pires, Sidonio Antonio; Ena, Ouda Teda (Syntax Literate, 2024)
This study aimed to analyze Christopher Marlow’s poem “The Passionate Shepherd to His Love”. The poem was interpreted stylistically from the choice of words, sentence arrangements, and the poetic devices used by the writer to present his thoughts to the audience. The literary devices included in the analysis were symbolism, imagery, simile, metaphor, hyperbole, and other sound devices like alliteration, consonance, assonance, and rhyme. Moreover, the study also provided an analysis of the structure and theme of the poem. By conducting this research, the researchers were able to shed light on the literary approaches, sound devices such as symbolism, imagery, simile, metaphor, hyperbole, and other sound devices like alliteration, consonance, assonance, and rhyme, hidden meanings, and artistic worth of the Poem “The Passionate Shepherd to His Love” by Christopher Marlow.